Penerapan Metode Task-Based Learning dalam Pengembangan Bahan Ajar Bahasa Jepang: Implementation of Task-Based Learning Method in Developing Japanese Language Teaching Materials - Wismadewi, I Gusti Agung Galuh; Sudiana, I Nyoman; Putrayasa, Ida Bagus; Wisudariani, Ni Made Rai (ITScience (Information Technology and Science), 2024)
Task-Based Learning (TBL) is a language teaching method that emphasizes providing graded tasks adjusted to learning abilities. This article aims to observe task-based learning (TBL) implementation in Japanese language training in the Japanese Language Center class. This TBL method is applied by giving pre-tests and post-tests to 35 students. There are 3 (three) tasks observed in this learning: vocabulary, context-based meaning, and simple language structures. The results show that implementing TBL is suitable for Japanese language center classes with diverse backgrounds in Japanese language ability. In addition, these tasks have structured and continuous characteristics so that the difficulty level will be controlled, which will make vocabulary mastery easier. The use of the Task-Based Learning method can improve student learning achievement. In this case, student achievement increased after implementing the Task-Based Learning method because this method excited students to learn to speak Japanese; this can be seen from the results of student responses. As many as 69.1% of students stated that they agreed and enjoyed learning using the task-based learning method, which made them interested in the lesson and no longer hesitant to speak Japanese. The application of the Task-Based Learning (TBL) method in the development of Japanese language teaching materials has been proven to have a significant positive impact on improving student communication skills, learning motivation, and the quality of teaching materials.